2006
DOI: 10.1080/13685530600804091
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in older men: A gender-based review

Abstract: Cancer is a common condition of the older male. Risk factors for developing a malignancy include genetic, environmental and life style features. Cancer epidemiology and prognosis differ depending on the age and gender of the population being studied. In the group of men older than 65 years, the most common malignant tumors are prostate, lung, colon and pancreatic cancer. Treatment options vary depending on the stage of the tumor when it is diagnosed, and the decision for therapeutic versus palliative intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Interestingly we observed that age-matched men from the highest SEIFA quintile were at an increased risk of ever having cancer. In surveillance studies, lower SEIFA quintiles have generally been shown to associate with increased morbidity and mortality [ 44 ]. It has been argued that improvements in recent years in cancer screening and awareness may have created an artificially high impression of cancer prevalence amongst affluent American men [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly we observed that age-matched men from the highest SEIFA quintile were at an increased risk of ever having cancer. In surveillance studies, lower SEIFA quintiles have generally been shown to associate with increased morbidity and mortality [ 44 ]. It has been argued that improvements in recent years in cancer screening and awareness may have created an artificially high impression of cancer prevalence amongst affluent American men [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the high expression level of SCIN in prostate cancer may be involved in the pathogenesis of prostate cancers. Previous studies suggest that prostate cancer is associated with age and gender of patients (21,22). To investigate the association of SCIN expression with these two factors, we analyzed the SCIN expression level in prostate cancer tissues with different factors.…”
Section: Scin Is Highly Expressed In Prostate Cancermentioning
confidence: 99%
“…Five-year survival for colorectal cancer is between 50-60 %, with females experiencing better survival rates than males despite the fact that women tend to be diagnosed with more advanced cancer compared with men [23][24][25]. Survival following diagnosis relates in part to the location of the cancer, with better prognosis for distal cancers -that is cancers that are further away from the centre of the body.…”
Section: Survivalmentioning
confidence: 95%